INTERSUBJECTIVITY AND EMBODIMENT IN THE FIELD OF PSYCHOTHERAPY - Kata Dóra KISS (Studia Universitatis Babeș-Bolyai. Philosophia)
Intersubjectivity is one of the most important concepts of the phenomenological school of thought. The approach assumes that our being in the world is based on relations with Others. The idea has a central role not only in the philosophy of perception but in psy-sciences as well. Mostly all branches of psychology agree that the self is constituted by its relations. However, there is much less consensus on how decisive these relations are. Therefore, the question of intersubjectivity has become the question of how we perceive human beings: as biological or social entities. Psy-sciences have never had one coherent and consensual paradigm, although nowadays the natural scientific standards are the most prevailing in the field, which prioritizes biological explanations over socio-cultural aspects. The study attempts to connect the phenomenological approach to intersubjectivity to the psychological approach to embodiment. For this, first, it elaborates on an essential problem of psy-sciences, transmitted by classical philosophy, namely the mind-body dualism, which implicitly establishes the current paradigm. Then, it aims to describe how the phenomenological approach, especially the philosophy of Maurice Merleau-Ponty, could dissolve the classical dualism through the assumption of the body-mind-world unity. Merleau-Ponty was one of those thinkers of the 20th century who laid down the foundations of the scientific paradigm of embodiment. Afterward, I illustrate the phenomenological concept above through Ben Rumble’s psychological approach, which applies the embodiment paradigm for the therapeutic process as a professional. The final part of the study attempts to establish a relation between the psychological attitude based on embodiment and the psychoanalytic theory of Sándor Ferenczi, the Hungarian psychoanalyst.